A revision of lithium minerals thermodynamics: Possible implications for fluids geochemistry and geothermometry. (January 2022) - Boschetti, Tiziano
Highlights: Thermodynamic parameters of 11 Li-minerals are reviewed and/or recalculated. Hint of improvements on geothermometric calculation of hot fluids are demonstrated. Multimineral equilibria involving ephesite and cookeite occurs in El Tatio fluids. Elbaite-ephesite equilibrium buffer the Li concentration at South Crofty Mine fluid. Abstract: In this study, the thermodynamic data of some lithium (Li) minerals (bikitaite, cookeite, elbaite, ephesite, hectorite, lepidolite, Li-mica, petalite, polylithionite, taeniolite, zinnwaldite) are revised. Despite the economic importance of lithium worldwide and the availability of some standard thermodynamic parameters of lithium minerals, a reluctance persists to include solubility data at different temperatures (logK) in hydrogeochemical calculation codes. The previously published standard thermodynamic data are reviewed, averaged and/or recalculated. Thereafter, the logK values are calculated and formated to be included into the thermodynamic dataset of two hydrogeochemical codes (The Geochemist's Workbench; PHREEQC). The interested reader has the possibility of reviewing and reworking them for other specific software. Finally, understanding the lithium geochemistry and geothermometry of the geothermal waters from El Tatio (northern Chile) and South Crofty Mine (Cornwall, UK) are discussed.